Study of some physiological activities for multimetal tolerant bacteria under metallic stress - Alhammadi, Eeman; Halimoon, Normala; Zulkeflee, Zufarzaana; Johari, Wan Lutfi Wan (Cosmos Scholars Publishing House, 2023)
Electroplating effluents contain heavy metals besides nitrate, which can be harmful to aquatic and terrestrial life if released into the environment. Bioremediation is an imperative task to remove these contaminants from aquatic surfaces. Bacterial species that are tolerant to multiple metals were isolated from electroplating effluents and studied for their ability to withstand high metal concentrations and perform physiological activities. These activities included the production of carotenoid pigments and the reduction of nitrate during exponential and stationary growth phases after exposure to high concentrations of single and quaternary metals. The influence of heavy metals on these activities and bacterial behavior was evaluated. The results showed that the production of carotenoid pigments increased over time, with the highest quantities produced at 48 hours with Zn, Cu, and quaternary. Pigments produced vary with the different types of metals and their concentrations. The ratio of pigment extract to unladen metal cells was higher compared to laden metals cells. The isolates were also capable of reducing nitrate and producing nitrite, but high metal concentrations hindered the conversion of nitrite to nitrogen gas and accumulated great amounts of nitrite between the end of the exponential phase and the start of the stationary phase. The production of carotenoids allowed the bacteria to tolerate high metal concentrations and continue reducing nitrate. This study suggests that pigmented bacteria and aerobic denitrifiers have the potential for bioremediation and nitrate reduction, which can help clean and recover contaminated environments.